Results of the symposium " Systemic therapy of squamous cell carcinoma of the head and neck. In search of optimal solutions...", held within the framework of the VII Annual Congress of the Russian Society of Specialists in Head and Neck Tumors - article Editorial (Опухоли головы и шеи, 2021)
.